LATE PROTESTANT COMMUNITIES OF KHERSON REGION AND KYIV REGION THROUGH THE PRISM OF ORTHODOX HISTORIOGRAPHY, MID-19TH CENTURY – EARLY 20TH CENTURY (Південний архів (історичні науки), 2024)
Protestantism is one of the most widespread religious denominations in Ukraine. Аccording to the Razumkov Center, as of 2022, is the third largest after Orthodoxy and Greek Catholicism. Protestant Ukrainian communities are divided into early Protestant (Lutherans, Calvinists, Mennonites) and late Protestant (Baptists, Pentecostals, Adventists). Communities of late Protestants in Ukraine make up the vast majority of all Protestants and are active participants in the social and religious life of the state. The study of their history, philosophy, and influence is a popular topic both in the academic and intra-Protestant circles. The pioneers of the study of late Protestantism in Ukraine were the leaders of the Orthodox Church of the Kherson and Kyiv dioceses, who were the first to encounter the emergence of a new doctrine among their faithful. Therefore, their works are the basis for historiographical studies of Ukrainian late Protestant communities. The purpose of the article is to systematically analyze the historiography of the Late Protestant problem in the works of the hierarchs of the Orthodox Church of the Russian Empire in the second half of the nineteenth and early twentieth centuries. Various historical methods were used in the study. The comparative-historical method was used to identify common and distinctive features in the studies of late Protestant communities by Orthodox hierarchs: analysis of issues, sources used, methodological approaches, etc. The historical and genetic method allows us to study the evolutionary processes in the Orthodox anti-Protestant literature caused by socio-political changes in the state. The result of the study is the consolidation in one article of the works of Orthodox hierarchs who studied the late Protestant communities of the Kherson and Kyiv regions in the mid-nineteenth and early twentieth centuries, which are conditionally divided into two areas: historical and religious studies. They are an integral part of the historiography of any scientific work on this topic. Therefore, this work is intended to greatly facilitate the search for future researchers. The scientific conclusion of the article is that the emergence of reform movements in Ukraine gave rise to a new trend in Orthodox literature – anti-Protestant. This had several far-reaching consequences: a detailed and comprehensive study of the history and doctrine of Protestant communities; simplification of Orthodox theological practice to a minimum that is understandable to both the preaching priest and the listening peasant; publication and reference to a large array of historical sources on late Protestantism in Ukraine, which have been preserved only partially.
Keywords: Stundism, Baptism, missionary, doctrine, theological academy.